Keabsahan Akad Jual Beli Terhadap Kebutuhan Pokok Masyarakat Era 5.0 di Tiktok Shop - Ningrum, Eka Rahayu Puspita; Hanifuddin, Iza (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Along with technological advances, it has a full impact on changes in civilizational lifestyles. Humans seem to be required to live in an instant world. Even cruelly, humans are served with various conveniences to achieve every desire they have without having to know about the meaning of social life. In this 5.0 era, Tiktok Shop is present as one of the days of technology organizationwith the sophistication of various features to make it easier for everyone to achieve their wants and needs efficiently and effectively. However, it is not uncommon to find cases that bring a ratan to every circle. Such as fraud committed to objects of interest because transactions are carried out in cyberspace. With phenomenal research methods and descriptive research on these problems, researchers conducted a study on the validity of buying and selling contracts on one of the Tiktok Shop platforms based on Islamic law. The results of this study show that in Islamic sharia, the buying and selling contract on the Tiktok Shop platform is valid because it can fulfill the pillars in the buying and selling contract. However, the level of validity does not guarantee the security of business transactions on the platform.